Analisis Inovasi Kewirausahaan dalam Film Gampang Cuan - Fadli Faturrahman (CV. Aksara Global Akademia, 2025)
Innovation in entrepreneurship is not only limited to the creation of new products or services, but also includes the development of more efficient business models, more effective marketing strategies, and new ways of managing resources. The film